1966
DOI: 10.1128/aem.14.4.539-551.1966
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Levels and Types of Microbial Contamination Detected in Industrial Clean Rooms

Abstract: Comparative levels and types of microbial contamination detected in industrial clean rooms. Appl. Microbiol. 14:539-551. 1966.-The primary objective of this study was to determine quantitatively and qualitatively the predominant types of microbial contamination occurring in conventional and laminar flow clean rooms. One horizontal laminar flow, three conventional industrial clean rooms, and three open factory areas were selected for microbiological tests. The results showed that as the environment and personne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1968
1968
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 2 publications
1
23
0
Order By: Relevance
“…In industry Sykes (1970) has pointed out that a room can be designed and maintained 'virtually sterile' tintil it is occupied by himians; such conditions are required for sterile filling of injectable materials. Favero et al (1966) have reported essentially similar studies whilst Behagel & Berg (1973) reported on the difficulty of maintaining staphylococcal cultures free from the risk of contamination by phage derived from strains carried by personnel. In a hospital situation the gravest risk is in the operating theatre (Payne, 1967;Ayliffe & Collins, 1967;Charnley, 1973), but there is also a general risk in the excessive dispersal of organisms into the air of wards (Hamburger, Green & Hamburger, 1945;Schaffner et al, 1969).…”
Section: Dispersal As a Hazardmentioning
confidence: 91%
“…In industry Sykes (1970) has pointed out that a room can be designed and maintained 'virtually sterile' tintil it is occupied by himians; such conditions are required for sterile filling of injectable materials. Favero et al (1966) have reported essentially similar studies whilst Behagel & Berg (1973) reported on the difficulty of maintaining staphylococcal cultures free from the risk of contamination by phage derived from strains carried by personnel. In a hospital situation the gravest risk is in the operating theatre (Payne, 1967;Ayliffe & Collins, 1967;Charnley, 1973), but there is also a general risk in the excessive dispersal of organisms into the air of wards (Hamburger, Green & Hamburger, 1945;Schaffner et al, 1969).…”
Section: Dispersal As a Hazardmentioning
confidence: 91%
“…However, working shoes were not used exclusively inside the greenhouse, but were also worn to go from one facility to another. Shoes have seldom been mentioned as vehicles of contamination in food production areas (8). This dissemination mechanism of enteric pathogens should be considered as an important control point during working procedures in greenhouses.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, shoes carrying animal feces positive for Salmonella (F serogroup strains) may be vehicles of contamination into the greenhouses. A discreet, but important number of samples from puddles (8) and soil (11) were also positive for pulsotypes isolated from tomatoes. As noted by Baloda et al (1) and Wonderling et al (22), some pulsotypes may be more able to adapt and survive on specific environments of production facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Even when personnel and density activity were high and samplers were placed downstream from personnel the maximum level of viable particles per cubic foot of air was about 1-2 in horizontal laminar flow clean rooms. Under similar circumstances in vertical laminar flow clean rooms it was not uncommon to detect less than [5][6][7][8][9][10] viable particles per 100 cubic feet of air. These contamination levels were several orders of magnitude lower than those obtained in conventional clean rooms and surgical suites.…”
Section: Laminar Flow Systemsmentioning
confidence: 99%